2016
DOI: 10.1016/j.virol.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-proteasome system is essential for the productive entry of Japanese encephalitis virus

Abstract: The host-virus interaction during the cellular entry of Japanese encephalitis virus (JEV) is poorly characterized. The ubiquitin-proteasome system (UPS), the major intracellular proteolytic pathway, mediates diverse cellular processes, including endocytosis and signal transduction, which may be involved in the entry of virus. Here, we showed that the proteasome inhibitors, MG132 and lactacystin, impaired the productive entry of JEV by effectively interfering with viral intracellular trafficking at the stage be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…Our previous quantitative proteomic analysis found that multiple host proteins involved in the UPS were regulated in JEV-infected cells, and further functional study indicated that RanBP2, an E3 ligase, can affect JEV replication (11). Our recent work found that the UPS plays an important role in the JEV entry process (55).…”
Section: Discussionmentioning
confidence: 90%
“…Our previous quantitative proteomic analysis found that multiple host proteins involved in the UPS were regulated in JEV-infected cells, and further functional study indicated that RanBP2, an E3 ligase, can affect JEV replication (11). Our recent work found that the UPS plays an important role in the JEV entry process (55).…”
Section: Discussionmentioning
confidence: 90%
“…Screening of an FDA-approved drug library for inhibitors of JEV infection. Recombinant viral particles (RVPs) with the luciferase-reporting replicon enveloped by the JEV structural proteins were used to select inhibitors, with a focus on those that inhibit virus entry and replication, by a high-throughput screening (HTS) assay (4,5). The number of genomic RNA copies of RVP was determined to be 8.4 ϫ 10 6 copies/ml by using a standard curve generated with plasmids carrying the infectious clone.…”
Section: Resultsmentioning
confidence: 99%
“…JEV strain AT31, the WNV replicon, and the DENV-2 replicon expressing Renilla luciferase (Rluc) were kindly provided by Bo Zhang, Wuhan Institute of Virology, Chinese Academy of Sciences (CAS), China. JEV replicon recombinant viral particles (RVPs) were generated as previously described (4,5). ZIKV strain H/PF/2013, kindly provided by the European Virus Archive Goes Global, was propagated and titrated in Vero cells.…”
Section: Methodsmentioning
confidence: 99%
“…By using this efficient approach the authors identified 286 genes which are involved in mechanism of JEV infection [216]. Based on in vivo studies in mice model, it is observed that bortezomib, an anticancer drug indicated for multiple myeloma and lymphoma can lower JEV-induced death in mice, along with alleviating the suffering in JEV infection and also reduce the brain damage possibly by proteasome inhibition [217,218]. This study highlights the possibility of a new drug candidate for JEV treatment.…”
Section: Drug Repurposing For Infectious Diseasesmentioning
confidence: 96%